Observations on Natural Reproduction of Teak - Kadambi, K. (Indian Forester, 1959)
This paper deals with the influences of the climatic, edaphic and biotic factors on the natural reproduction of teak in India. The structural composition of the seed, its germination and the establishment of the seedling are critically examined in relation to the inception and establishment of natural regeneration, and known instances of the occurrence of natural reproduction in different parts of India have been pointed out. The paper ends with a pointer to the need for a closer study of this question.